2008
DOI: 10.1007/s11095-008-9545-z
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin Impairs Constitutively Active TGFα-EGFR Autocrine Loop in Advanced Human Prostate Carcinoma Cells

Abstract: This study, for the first time, identifies the inhibitory effect of silibinin on constitutively active TGFalpha-EGFR autocrine loop in advanced human PCA cells, which plausible contributes to the strong efficacy of silibinin in PCA prevention and intervention, as reported in recent studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 29 publications
(44 reference statements)
2
18
0
2
Order By: Relevance
“…Previous studies showed that silibinin could inhibit EGFR activity through various mechanisms such as suppression of ligand binding (30) or reduction of ligand expression (31). The present observations show that the inhibitory effect of silibinin on EGFR and Akt activity can also be observed in lung cancer cells.…”
Section: Discussionsupporting
confidence: 71%
“…Previous studies showed that silibinin could inhibit EGFR activity through various mechanisms such as suppression of ligand binding (30) or reduction of ligand expression (31). The present observations show that the inhibitory effect of silibinin on EGFR and Akt activity can also be observed in lung cancer cells.…”
Section: Discussionsupporting
confidence: 71%
“…Treatment of prostate cancer cells with silibinin abrogated constitutive activation of STAT-3 in DU145 cells (99), disrupted EGFR signaling in LNCaP and DU145 cells (100,101), targeted IGFR signaling in PC3 cells (102), the Wnt/β-catenin pathway in PC3 and DU145 cells (103), and AR signaling in LNCaP cells both directly by reducing nuclear localization of the receptor (104) and indirectly through downregulation of a co-activator, prostate epitheliumderived Ets transcription factor (105,106). Disruption of EGF signaling by silibinin in prostate cancer cells was associated with a decrease in secreted transforming growth factor-α and modulation of MAPK activity of both ERK1/2 and JNK1/2 (101). Disruption of the Wnt/β-catenin pathway involved modulation of a co-receptor, the low-density lipoprotein receptor-related protein-6 (LRP6) (103).…”
Section: Silibinin Effects On Cell Signaling In Prostate Cancer Cellsmentioning
confidence: 99%
“…Based on the inhibitory effect of silibinin on EGFR transactivation in response to hypertrophic stimuli [Hannay and Yu, 2003;Tyagi et al, 2008], we further assessed its effect on the downstream signaling targets such as MAPK and PI3K/Akt/GSK3b pathways. Our data showed that ERK1/2, JNK1/2, and p38 were significantly phosphorylated both in Ang II-treated cardiomyocytes and in AB mice.…”
Section: Effects Of Silibinin On Mapks and Pi3k/akt/gsk3b Signaling Imentioning
confidence: 99%
“…However, the effect of silibinin on cardiac hypertrophy and the related signaling mechanisms still remain unclear. Although silibinin has been shown to inhibit EGFR activation, very little is known about whether this inhibitory effect is related to the protective role in cardiac hypertrophy Tyagi et al, 2008]. Therefore, we aimed to determine whether silibinin attenuates cardiac hypertrophy in vitro and in vivo by interfering EGFR-dependent pathways.…”
mentioning
confidence: 99%